Non-invasive assessment of effects of isosorbide dinitrate on left ventricular diastolic functions and left atrial systolic time intervals in hypertensive patients - Demir, A.; Luleci, C.; Isik, A.; Donder, E.; Arslan, N.; Celiker, H. (My University, 1990)
[Abstract Not Available]
Keywords: isosorbide dinitrate; article; controlled study; diastole; drug effect; female; heart left atrium pressure; heart left ventricle function; human; hypertension; major clinical study; male